Light heating super-hydrophobic coating and preparation method thereof
By combining modified fluorosilicone resin and nano-scale carbon-based materials, superhydrophobic coatings with photothermal conversion capabilities were prepared, which solved the problem of single performance and insufficient corrosion resistance of existing coatings, and achieved versatility and efficient prevention Ice and deicing effect.
Patent Information
- Application Number
- CN202411382672.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-30
AI Technical Summary
In the anti-icing process, existing superhydrophobic coatings have problems such as single performance, poor corrosion resistance and insufficient wear and weather resistance in the anti-icing process, and it is difficult to effectively combine the light-thermal ice-proof and superhydrophobic effects.
Using modified fluorosilicone resin, modified nano-grade carbon-based materials, polypyrrole resin and nano-silica, a superhydrophobic coating with photothermal conversion capability is prepared through polymerization and modification treatment, combined with hydrophobic silicon dioxide. and filler additives to form a coating with excellent corrosion resistance, wear resistance and light heating properties.
It realizes the versatility of the coating, has light-thermal anti-icing, super-hydrophobic deicing and long-term anti-corrosion properties, and is suitable for different application scenarios, reducing the dependence of a variety of coatings and the cost of repeated construction, and is easy to control.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrophobic coatings, and in particular to a photothermal super hydrophobic coating and a preparation method thereof. Background Art
[0002] Surface ice is a common natural phenomenon, but it often causes serious damage to infrastructure and industrial equipment. In particular, surface ice can have a great impact on power transportation, aviation, wind turbines and ocean-going ships, and may also cause disasters such as energy consumption, emergencies, and safety hazards. Traditional deicing methods include mechanical deicing, microwave deicing and manual deicing, but they are generally inefficient and energy-intensive.
[0003] Because of its micro-nano structure on the surface, the super-hydrophobic coating can remove water droplets in the condensation stage to delay ice nucleation and reduce ice accumulation, but the micro-nano structure will form a mechanical interlocking structure with ice, increase the adhesion strength of ice and material surface, and make it difficult to remove ice under the external force of gravity, wind and vibration. At the same time, if the traditional mechanical method is used to de-ice on the super-hydrophobic surface, the physical contact will have a huge impact on the surface, resulting in the destruction of the micro-nano structure on the surface of the material, and the anti-icing function will be attenuated. There are certain limitations in the anti-icing process of a single hydrophobic surface, so the non-contact remote lighting method is more gentle and lasting, but the non-contact remote lighting method is not easy to implement during implementation. Photothermal materials have high photothermal conversion efficiency and no chemical pollution, and have the advantages of energy saving and environmental protection. They are gradually attracting attention in the field of anti-icing materials. Therefore, the coating with a combination of photothermal anti-icing and super-hydrophobic effects has broad application prospects, but there are few coatings that combine photothermal anti-icing and super-hydrophobic effects in the prior art. In addition, the existing super-hydrophobic coatings also have poor corrosion resistance and cannot meet the requirements of wear and weather resistance.
[0004] Therefore, there is an urgent need to synthesize a photothermal super-hydrophobic coating, which can not only make up for the shortcomings of super-hydrophobic coatings that can only repel water but cannot perform photothermal conversion and have a single performance, but also increase the corrosion resistance, wear resistance and weather resistance of the coating. Summary of the invention
[0005] To solve the above problems, the object of the present invention is to provide a photothermal super-hydrophobic coating and a preparation method thereof.
[0006] In order to achieve the above object, the present invention is implemented through the following technical solutions: A photothermal super-hydrophobic coating is composed of the following raw materials, in parts by weight: 30 to 40 parts of a modified fluorosilicone resin solution, 20 to 30 parts of a modified nano-scale carbon-based material, 3 to 5 parts of a functional additive, 3 to 15 parts of a polypyrrole resin, 0.1 to 0.8 parts of an adhesion promoter, 0.05 to 0.1 parts of nano-silicon dioxide, 15 to 25 parts of a filler, and 25 to 35 parts of a first organic solvent; The modified fluorosilicone resin solution is prepared according to the following steps: Add methacrylic acid acyloxypropyl trimethoxysilane, ester-containing benzoxazine monomer, fluorine-containing acrylate monomer and solvent ethyl acetate into a reactor, introduce nitrogen gas under stirring, add initiator-ethyl acetate solution into the reactor several times after 15-20 minutes, raise the temperature to 75-85° C. after the addition is complete, react for 12-24 hours to obtain a reaction solution, and place the obtained reaction solution at 30-40° C. and vacuum dry for 8-10 hours to obtain a modified fluorosilicone resin; The obtained modified fluorosilicone resin is dissolved in a second organic solvent to prepare a modified fluorosilicone resin solution with a solid content of 30-60%; The fluorine-containing acrylic monomer is dodecafluoroheptyl methacrylate or / and perfluorobutyl ethyl methacrylate; The initiator is AIBN or BPO, the amount of the initiator is 0.1-2% of the monomer mass, and the mass ratio of the initiator to ethyl acetate in the initiator-ethyl acetate solution is 1:8-10; The mass ratio of the methacrylate acyloxypropyloxysilane, the ester-containing benzoxazine monomer and the fluorine-containing acrylate monomer is 8-15:5-12:18-25; The amount of solvent ethyl acetate used is 50-60% of the total mass of the monomers; The second organic solvent is ethyl acetate or dichloromethane; The modified nano-scale carbon-based material is obtained by modifying an oxidized nano-scale carbon-based material with silane; the carbon-based material is carbon black or carbon nanotubes.
[0007] Preferably, the functional additive is two or three of a wetting and dispersing agent, a defoaming agent and a leveling agent. Further preferably, the wetting and dispersing agent is a nonionic wetting and dispersing agent or a fluorocarbon wetting agent, such as Genisperse 7742, Patcham® 9060, FC-5503, Silok® 7630, 4010, 505s; the defoaming agent is a mineral oil defoaming agent, a silicone defoaming agent or a polyether defoaming agent, such as Skytech® SAT80, RB-5209, Rhodoline DF4226, 2503; the leveling agent is a silicone oil leveling agent or a polyether leveling agent, such as FDG-513, WE-D8939, AMORSO-137, AFCONA3596, 3700, 2050.
[0008] Preferably, the adhesion promoter is silane coupling agent Z-6121 or titanate coupling agent; the titanate coupling agent is isopropyl triisostearyl titanate or isopropyl tri(dioctyl pyrophosphate) titanate.
[0009] Preferably, the filler is a mixture of two or more of heavy calcium, talc, barium sulfate, sericite powder and carbon black.
[0010] Preferably, the first organic solvent is one or more of butyl acetate, ethyl acetate or dichloromethane.
[0011] Preferably, the specific preparation process of the modified nanoscale carbon-based material is: The nano-scale carbon-based material is slowly added to the mixed strong acid in small amounts and multiple times, heated to 58-62°C under mechanical stirring, stirred for reaction for 12-24 hours, washed to neutrality, and dried to obtain the oxidized nano-scale carbon-based material; Ultrasonic dispersion of the obtained oxidized nano-scale carbon-based material in ethanol, adding a second silane coupling agent thereto under stirring, continuing stirring for 0.5 to 1 hour, filtering, washing with ethanol, and drying under vacuum to obtain a modified nano-scale carbon-based material; The mass ratio of the nano-scale carbon-based material, the mixed strong acid and the second silane coupling agent is 1:100~150:0.03~0.06; The mixed strong acid is obtained by mixing concentrated sulfuric acid and concentrated nitric acid in a mass ratio of 100:40-50.
[0012] Preferably, the second silane coupling agent is one or more of silane coupling agents KH560, KH570 or KH550.
[0013] The present invention also includes a method for preparing a photothermal super-hydrophobic coating, comprising the following steps: mixing, by weight, 0.1 to 0.8 parts of an adhesion promoter, 15 to 25 parts of a filler and 25 to 35 parts of a first organic solvent, grinding to less than 40 μm, filtering, adding 30 to 40 parts of a modified fluorosilicone resin solution, 3 to 15 parts of a polypyrrole resin, 20 to 30 parts of a modified nanoscale carbon-based material, 0.05 to 0.1 parts of nano-silicon dioxide, and 3 to 5 parts of a functional additive, stirring and dispersing the mixture evenly to obtain a photothermal super-hydrophobic coating.
[0014] Compared with the prior art, the present invention has the following advantages: The light-heating super-hydrophobic coating of the present invention is doped with modified photothermal materials, and the surface of the coating has a surface micro-nano structure after drying, and has super-hydrophobic performance. First, the present invention adopts polysiloxane and fluorine-containing monomers to form fluorosilicone block polymers, and introduces benzoxazine monomers in the structure as anticorrosive resin matrix to prepare modified fluorosilicone resin solution, introduces photothermal layer by adding modified carbon-based materials, and prepares sprayable super-hydrophobic coatings in combination with hydrophobic silica and filler additives. Secondly, carbon black, carbon nanotubes are used in the coating to convert light energy, the characteristics of nano-silicon dioxide hydrophobicity, and polypyrrole is added in the resin system to further ensure the light-heating performance of the coating. The surface energy of the fluorine silicon element itself, and the ring-opening polymerization of the benzoxazine resin itself, make the coating itself have excellent corrosion resistance, wear resistance and weather resistance and other properties.
[0015] The photothermal super-hydrophobic coating of the present invention can be sprayed on substrates of various materials and shapes, with strong adhesion and no cracking. The photothermal super-hydrophobic coating of the present invention integrates multiple functions such as photothermal anti-icing, super-hydrophobic deicing, and long-term anti-corrosion, and can meet the anti-icing and sticking requirements in different application scenarios, reducing the dependence on multiple coatings and the cost of repeated construction. This coating has the multifunctional integration of photothermal super-hydrophobic deicing and long-term anti-corrosion performance, and is easy to operate and controllable. DETAILED DESCRIPTION
[0016] The purpose of the present invention is to provide a photothermal super-hydrophobic coating and a preparation method thereof, which is achieved by the following technical solutions: The following are some manufacturers of additives Wetting and dispersing agent: Genisperse 7742 Nanjing Shangqin New Materials Technology Co., Ltd., Patcham® 9060 Shierli Coatings, FC-5503 Guangdong Zhongxiang New Materials Co., Ltd., Silok® 7630 Siluoke New Materials Co., Ltd., 4010 Efcona, 505s Guangzhou Situyuan Chemical Co., Ltd.; Defoaming agent: Skytech® SAT80 Zhonghaojing Polymer New Materials Co., Ltd., RB-5209 Leibang High-tech Materials Co., Ltd., Rhodoline DF4226 Liantuo Blueprint, Leveling agent: FDG-513 Fangding New Materials Co., Ltd., WE-D8939 Anhui Jiazhi Xinnuo Chemical Co., Ltd., AMORSO-137 Jijiyan Shandong New Materials Co., Ltd., AFCONA 3596 Efcona Polymer Co., Ltd., 3700 Efcona, 2050 Guangzhou Si Tuyuan Chemical Co., Ltd. Isopropyl triisostearyl titanate, also known as isopropyl triisostearate titanate.
[0017] The polypyrrole resin is a common polypyrrole resin available on the market, such as those sold by Xi'an Qiyue Biotechnology Co., Ltd. and Xi'an Ruixi Biotechnology Co., Ltd.
[0018] The ester-containing benzoxazine monomer was prepared based on the second chapter of Shandong University's master's thesis: Synthesis and Properties of Ester-containing Benzoxazine and Its Polymers.
[0019] The concentrated sulfuric acid and concentrated nitric acid described in the present invention are commercially available. Generally, the mass concentration of the concentrated sulfuric acid is about 98%, and the mass concentration of the concentrated nitric acid is about 68%.
[0020] The present invention is further described below in conjunction with specific embodiments. Example 1
[0021] A photothermal super-hydrophobic coating, composed of the following raw materials: 30 kg of modified fluorosilicone resin solution, 20 kg of modified nano-scale carbon-based material, 1 kg of wetting and dispersing agent Genisperse 7742, 2 kg of defoaming agent Skytech® SAT80, 3 kg of polypyrrole resin, 0.1 kg of silane coupling agent Z-6121, 0.05 kg of nano-silicon dioxide, 5 kg of heavy calcium, 10 kg of talc and 25 kg of butyl acetate; The modified fluorosilicone resin solution is prepared according to the following steps: 4 kg of methacrylic acid acyloxypropyl trimethoxysilane, 2.5 kg of ester-containing benzoxazine monomer, 9 kg of methacrylate dodecafluoroheptyl ester and 7.75 kg of ethyl acetate were added to a reactor, and nitrogen was introduced under stirring. After 15 minutes, an initiator-ethyl acetate solution was added to the reactor in several batches. After the addition was completed, the temperature was raised to 75° C. and reacted for 12 hours to obtain a reaction solution. The obtained reaction solution was placed at 30° C. and vacuum dried for 8 hours to obtain a modified fluorosilicone resin; 9 kg of the obtained modified fluorosilicone resin was dissolved in 21 kg of ethyl acetate to obtain a modified fluorosilicone resin solution; The initiator-ethyl acetate solution is obtained by dissolving 15.5 g of AIBN in 124 g of ethyl acetate; The modified nano-scale carbon-based material is obtained by modifying an oxidized nano-scale carbon-based material with silane; and the carbon-based material is carbon black. Example 2
[0022] A photothermal super-hydrophobic coating, composed of the following raw materials: 40 kg of modified fluorosilicone resin solution, 30 kg of modified nano-scale carbon-based material, 3 kg of wetting and dispersing agent Patcham® 9060, 1 kg of defoaming agent RB-5209, 1 kg of leveling agent FDG-513, 15 kg of polypyrrole resin, 0.8 kg of isopropyl triisostearyl titanate, 0.1 kg of nano-silicon dioxide, 10 kg of barium sulfate, 15 kg of sericite powder and 35 kg of ethyl acetate; The modified fluorosilicone resin solution is prepared according to the following steps: 7.5 kg of methacrylic acid acyloxypropyl trimethoxysilane, 6 kg of ester-containing benzoxazine monomer, 12.5 kg of perfluorobutyl ethyl methacrylate and 15.6 kg of ethyl acetate were added to a reactor, and nitrogen was introduced under stirring. After 20 minutes, an initiator-ethyl acetate solution was added to the reactor in several batches. After the addition was completed, the temperature was raised to 85° C. and reacted for 24 hours to obtain a reaction solution. The obtained reaction solution was placed at 40° C. and vacuum dried for 10 hours to obtain a modified fluorosilicone resin; 24 kg of the obtained modified fluorosilicone resin was dissolved in 16 kg of dichloromethane to prepare a modified fluorosilicone resin solution; The initiator-ethyl acetate solution is obtained by dissolving 0.52 kg of BPO in 5.2 kg of ethyl acetate; The modified nano-scale carbon-based material is obtained by modifying the oxidized nano-scale carbon-based material with silane; the carbon-based material is a carbon nanotube. Example 3
[0023] A photothermal super-hydrophobic coating, composed of the following raw materials: 32 kg of modified fluorosilicone resin solution, 22 kg of modified nano-scale carbon-based material, 1 kg of wetting dispersant FC-5503, 1 kg of defoaming agent Rhodoline DF4226, 1.5 kg of leveling agent WE-D8939, 4 kg of polypyrrole resin, 0.2 kg of isopropyl tris (dioctyl pyrophosphate acyloxy) titanate, 0.06 kg of nano-silica, 8 kg of sericite powder, 8 kg of carbon black and 12 kg of dichloromethane; The modified fluorosilicone resin solution is prepared according to the following steps: 4 kg of methacrylate acyloxypropyl trimethoxysilane, 2.4 kg of ester-containing benzoxazine monomer, 4 kg of dodecafluoroheptyl methacrylate, 4 kg of perfluorobutylethyl methacrylate fluorinated acrylate monomer and 7.5 kg of ethyl acetate were added to a reactor, and nitrogen was introduced under stirring. After 16 minutes, an initiator-ethyl acetate solution was added to the reactor in several batches. After the addition was completed, the temperature was raised to 78° C. and the reaction was carried out for 15 hours to obtain a reaction solution. The obtained reaction solution was placed at 32° C. and vacuum dried for 8.5 hours to obtain a modified fluorosilicone resin; Dissolving 12.8 kg of the obtained modified fluorosilicone resin in 19.2 kg of ethyl acetate to obtain a modified fluorosilicone resin solution; The initiator-ethyl acetate solution is obtained by dissolving 0.072 kg of AIBN in 0.648 kg of ethyl acetate; The modified nano-scale carbon-based material is obtained by modifying the oxidized nano-scale carbon-based material with silane; the carbon-based material is a carbon nanotube, and specifically comprises the following steps: 22 kg of carbon nanotubes were slowly added to 2310 kg of mixed strong acid in small amounts and in multiple times, heated to 60°C under mechanical stirring, stirred for reaction for 15 hours, washed to neutrality, and dried to obtain oxidized nano-scale carbon-based materials; The obtained oxidized nano-scale carbon-based material was ultrasonically dispersed in 180 kg of ethanol, 0.44 kg of silane coupling agent KH560 and 0.44 kg of silane coupling agent KH570 were added thereto under stirring, and stirring was continued for 50 minutes, filtered, washed with ethanol, and dried under vacuum to obtain a modified nano-scale carbon-based material; The mixed strong acid is obtained by mixing concentrated sulfuric acid and concentrated nitric acid in a mass ratio of 100:45. Example 4
[0024] A photothermal super-hydrophobic coating, composed of the following raw materials: 38 kg of modified fluorosilicone resin solution, 26 kg of modified nano-scale carbon-based material, 1.1 kg of wetting and dispersing agent Silok®7630, 1.1 kg of defoaming agent 2503, 1 kg of leveling agent AMORSO-137, 10 kg of polypyrrole resin, 0.4 kg of isopropyl tri(dioctyl pyrophosphate acyloxy) titanate, 0.08 kg of nano-silicon dioxide, 5 kg of talc, 5 kg of barium sulfate, 10 kg of sericite powder, 14 kg of butyl acetate and 14 kg of dichloromethane; The modified fluorosilicone resin solution is prepared according to the following steps: 4.5 kg of methacrylic acid acyloxypropyl trimethoxysilane, 4 kg of ester-containing benzoxazine monomer, 5.5 kg of methacrylate dodecafluoroheptyl ester and 5.5 kg of ethyl acetate were added to a reactor, and nitrogen was introduced under stirring. After 18 minutes, an initiator-ethyl acetate solution was added to the reactor in several batches. After the addition was completed, the temperature was raised to 80° C. and reacted for 15 hours to obtain a reaction solution. The obtained reaction solution was placed at 35° C. and vacuum dried for 9 hours to obtain a modified fluorosilicone resin; 19 kg of the obtained modified fluorosilicone resin was dissolved in 19 kg of dichloromethane to prepare a modified fluorosilicone resin solution; The initiator-ethyl acetate solution is obtained by dissolving 0.117 kg of BPO in 1 kg of ethyl acetate; The modified nano-scale carbon-based material is obtained by modifying the oxidized nano-scale carbon-based material with silane; the carbon-based material is nano-scale carbon black, and the specific process is as follows: 26 kg of nano-scale carbon black was slowly added to 2600 kg of mixed strong acid in small amounts and for multiple times, heated to 58°C under mechanical stirring, stirred for reaction for 24 hours, washed to neutrality, and dried to obtain oxidized nano-scale carbon black; The obtained oxidized nano-scale carbon black was ultrasonically dispersed in 250 kg of ethanol, 0.78 kg of silane coupling agent KH560 was added thereto under stirring, stirring was continued for 0.5 hours, filtered, washed with ethanol, and dried under vacuum to obtain a modified nano-scale carbon-based material; The mixed strong acid is obtained by mixing concentrated sulfuric acid and concentrated nitric acid in a mass ratio of 100:40. Example 5
[0025] A photothermal super-hydrophobic coating, composed of the following raw materials: 34 kg of modified fluorosilicone resin solution, 25 kg of modified nano-scale carbon-based material, 1.4 kg of wetting dispersant 4010, 1.2 kg of defoaming agent Skytech® SAT80, 1.2 kg of leveling agent AFCONA 3596, 6 kg of polypyrrole resin, 0.4 kg of silane coupling agent Z-6121, 0.07 kg of nano-silicon dioxide, 6 kg of heavy calcium, 6 kg of sericite powder, 6 kg of carbon black and 30 kg of ethyl acetate; The modified fluorosilicone resin solution is prepared according to the following steps: 4 kg of methacrylic acid acyloxypropyl trimethoxysilane, 3 kg of ester-containing benzoxazine monomer, 3 kg of dodecafluoroheptyl methacrylate, 4 kg of perfluorobutyl ethyl methacrylate and 7.7 kg of ethyl acetate were added to a reactor, and nitrogen was introduced under stirring. After 19 minutes, an initiator-ethyl acetate solution was added to the reactor in several batches. After the addition was completed, the temperature was raised to 78° C. and reacted for 20 hours to obtain a reaction solution. The obtained reaction solution was placed at 36° C. and vacuum dried for 9 hours to obtain a modified fluorosilicone resin; 11.9 kg of the obtained modified fluorosilicone resin was dissolved in 22.1 kg of dichloromethane to prepare a modified fluorosilicone resin solution; The initiator-ethyl acetate solution is obtained by dissolving 0.014 kg of BPO in 0.14 kg of ethyl acetate; The modified nano-scale carbon-based material is obtained by modifying the oxidized nano-scale carbon-based material with silane; the carbon-based material is a carbon nanotube, and the specific steps are as follows: 25 kg of carbon nanotubes were slowly added to 3750 kg of mixed strong acid in small amounts and in multiple times, heated to 62°C under mechanical stirring, stirred for reaction for 12 hours, washed to neutrality, and dried to obtain oxidized carbon nanotubes; The obtained oxidized carbon nanotubes were ultrasonically dispersed in 200 kg of ethanol, 1.5 kg of silane coupling agent KH570 was added thereto under stirring, stirring was continued for 1 hour, filtered, washed with ethanol, and dried under vacuum to obtain a modified nanoscale carbon-based material; The mixed strong acid is obtained by mixing concentrated sulfuric acid and concentrated nitric acid in a mass ratio of 100:50. Example 6
[0026] A photothermal super-hydrophobic coating, composed of the following raw materials: 35 kg of modified fluorosilicone resin solution, 25 kg of modified nano-scale carbon-based material, 1 kg of wetting dispersant 505s, 2 kg of defoaming agent RB-5209, 1 kg of leveling agent AFCONA 3700, 8 kg of polypyrrole resin, 0.5 kg of isopropyl triisostearyl titanate, 0.08 kg of nano-silicon dioxide, 10 kg of talc, 10 kg of carbon black, 15 kg of ethyl acetate and 15 kg of dichloromethane; The modified fluorosilicone resin solution is prepared according to the following steps: 4.5 kg of methacryloyloxypropyltrimethoxysilane, 4 kg of ester-containing benzoxazine monomer, 10 kg of fluorine-containing acrylate monomer and 10 kg of ethyl acetate were added to a reactor, and nitrogen was introduced under stirring. After 18 minutes, an initiator-ethyl acetate solution was added to the reactor in several batches. After the addition was completed, the temperature was raised to 82° C. and reacted for 20 hours to obtain a reaction solution. The obtained reaction solution was placed at 38° C. and vacuum dried for 9 hours to obtain a modified fluorosilicone resin; 15.75 kg of the obtained modified fluorosilicone resin was dissolved in 19.25 kg of ethyl acetate to prepare a modified fluorosilicone resin solution; The fluorine-containing acrylic monomer is dodecafluoroheptyl methacrylate or / and perfluorobutyl ethyl methacrylate; The initiator-ethyl acetate solution is obtained by dissolving 0.02 kg AIBN in 0.18 kg ethyl acetate; The modified nano-scale carbon-based material is obtained by modifying the oxidized nano-scale carbon-based material with silane; the carbon-based material is carbon black, and specifically comprises the following steps: 25 kg of carbon black was slowly added to 2600 kg of mixed strong acid in small amounts several times, heated to 60°C under mechanical stirring, stirred for reaction for 18 hours, washed to neutrality, and dried to obtain oxidized carbon black; The obtained oxidized carbon black was ultrasonically dispersed in 200 kg of ethanol, 1.25 kg of silane coupling agent KH550 was added thereto under stirring, stirring was continued for 45 minutes, filtered, washed with ethanol, and dried under vacuum to obtain a modified nanoscale carbon-based material; The mixed strong acid is obtained by mixing concentrated sulfuric acid and concentrated nitric acid in a mass ratio of 100:45. Example 7
[0027] The method for preparing the photothermal super-hydrophobic coating described in Example 1 comprises the following steps: 5 kg of heavy calcium, 10 kg of talc, 0.1 kg of silane coupling agent Z-6121 and 25 kg of butyl acetate were mixed, ground to less than 40 μm, filtered, and 30 kg of modified fluorosilicone resin solution, 20 kg of modified nano-scale carbon-based material, 3 kg of polypyrrole resin, 0.05 kg of nano-silica, 1 kg of wetting and dispersing agent Genisperse 7742 and 2 kg of defoaming agent Skytech®SAT80 were added thereto, stirred and dispersed evenly to obtain a light-heating super-hydrophobic coating. Example 8
[0028] The method for preparing the photothermal super-hydrophobic coating described in Example 2 comprises the following steps: 0.8 kg of isopropyl triisostearoyl titanate, 10 kg of barium sulfate, 15 kg of sericite powder and 35 kg of ethyl acetate were mixed, ground to less than 40 μm, filtered, and 40 kg of modified fluorosilicone resin solution, 30 kg of modified nano-scale carbon-based material, 3 kg of wetting and dispersing agent Patcham® 9060, 1 kg of defoaming agent RB-5209, 1 kg of leveling agent FDG-513, 15 kg of polypyrrole resin and 0.1 kg of nano-silica were added thereto and stirred and dispersed evenly to obtain a light-heating super-hydrophobic coating. Example 9
[0029] The method for preparing the photothermal super-hydrophobic coating described in Example 3 comprises the following steps: 0.2 kg of isopropyl tri(dioctyl pyrophosphate) titanate, 8 kg of sericite powder, 8 kg of carbon black and 12 kg of dichloromethane were mixed, ground to less than 40 μm, filtered, and 32 kg of modified fluorosilicone resin solution, 22 kg of modified nano-scale carbon-based material, 1 kg of wetting dispersant FC-5503, 1 kg of defoaming agent Rhodoline DF4226, 1.5 kg of leveling agent WE-D8939, 4 kg of polypyrrole resin and 0.06 kg of nano-silica were added and stirred and dispersed evenly to obtain a light-heating super-hydrophobic coating. Example 10
[0030] The method for preparing the photothermal super-hydrophobic coating described in Example 4 comprises the following steps: 0.4 kg of isopropyl tri(dioctyl pyrophosphate) titanate, 5 kg of talc, 5 kg of barium sulfate, 10 kg of sericite powder, 14 kg of butyl acetate and 14 kg of dichloromethane were mixed, ground to less than 40 μm, filtered, and 38 kg of modified fluorosilicone resin solution, 26 kg of modified nano-scale carbon-based material, 1.1 kg of wetting and dispersing agent Silok®7630, 1.1 kg of defoaming agent 2503, 1 kg of leveling agent AMORSO-137, 10 kg of polypyrrole resin and 0.08 kg of nano-silica were added thereto and stirred and dispersed evenly to obtain a light-heating super-hydrophobic coating. Embodiment 11
[0031] The method for preparing the photothermal super-hydrophobic coating described in Example 5 comprises the following steps: 0.4 kg of silane coupling agent Z-6121, 6 kg of heavy calcium, 6 kg of sericite powder, 6 kg of carbon black and 30 kg of ethyl acetate were mixed, ground to less than 40 μm, filtered, and 34 kg of modified fluorosilicone resin solution, 25 kg of modified nano-scale carbon-based material, 1.4 kg of wetting dispersant 4010, 1.2 kg of defoaming agent Skytech®SAT80, 1.2 kg of leveling agent AFCONA 3596, 6 kg of polypyrrole resin and 0.07 kg of nano-silica were added and stirred and dispersed evenly to obtain a light-heating super-hydrophobic coating. Example 12
[0032] The method for preparing the photothermal super-hydrophobic coating described in Example 6 comprises the following steps: 0.5 kg of isopropyl triisostearoyl titanate, 10 kg of talc, 10 kg of carbon black, 15 kg of ethyl acetate and 15 kg of dichloromethane were mixed, ground to less than 40 μm, filtered, and 35 kg of modified fluorosilicone resin solution, 25 kg of modified nano-scale carbon-based material, 1 kg of wetting dispersant 505s, 2 kg of defoaming agent RB-5209, 1 kg of leveling agent AFCONA 3700, and 8 kg of polypyrrole resin were added thereto, stirred and dispersed evenly to obtain a light-heating super-hydrophobic coating.
[0033] After spraying (thickness of 100 microns), the photothermal super-hydrophobic coating of the present invention was first cured in an oven at 120° C. for two hours and then cured at 180° C. for two hours to obtain a coating, and the following tests were performed. The results are shown in Table 1.
[0034] The detection steps of surface temperature after 10 minutes of 1sun illumination are as follows: use a 500W xenon lamp to simulate sunlight, irradiate the coating surface, and detect the temperature of the coating surface after ten minutes.
[0035] The surface contact angle is carried out in accordance with GB / T 30447-2013, the impact resistance test is carried out in accordance with GB / T 1732-2020, and the salt spray resistance test is carried out in accordance with GB10125-1997.
[0036] Table 1 Performance test results of the photothermal super-hydrophobic coatings obtained in Examples 7 to 12 Surface contact angle (°) Surface temperature after 1sun exposure for 10 minutes (℃) Adhesion (cross cut method) (grade) Salt spray resistance test 168h Impact resistance (50cm) Example 7 149 51.5 Level 0 No abnormality in paint film qualified Example 8 150 52.4 Level 0 No abnormality in paint film qualified Example 9 153 54.9 Level 0 No abnormality in paint film qualified Example 10 156 60.5 Level 0 No abnormality in paint film qualified Embodiment 11 158 62.8 Level 0 No abnormality in paint film qualified Example 12 155 61.4 Level 0 No abnormality in paint film qualified It can be seen from the results in Table 1 that the photothermal super-hydrophobic coating of the present invention has excellent hydrophobic properties, strong adhesion, excellent paint film mechanical properties, and the coating will heat up after being exposed to light, and has photothermal properties. The melted ice on the photothermal film can easily fall off the super-hydrophobic coating to avoid refreezing. The coating can be used for de-icing of pipelines, marine transportation, offshore platforms and other facilities.
Claims
1. A photothermal super-hydrophobic coating, characterized in that: The invention is composed of the following raw materials in parts by weight: 30-40 parts of modified fluorosilicone resin solution, 20-30 parts of modified nano-scale carbon-based material, 3-5 parts of functional additive, 3-15 parts of polypyrrole resin, 0.1-0.8 parts of adhesion promoter, 0.05-0.1 parts of nano-silicon dioxide, 15-25 parts of filler and 25-35 parts of first organic solvent; The modified fluorosilicone resin solution is prepared according to the following steps: Add methacrylic acid acyloxypropyl trimethoxysilane, ester-containing benzoxazine monomer, fluorine-containing acrylate monomer and solvent ethyl acetate into a reactor, introduce nitrogen gas under stirring, add initiator-ethyl acetate solution into the reactor several times after 15-20 minutes, raise the temperature to 75-85° C. after the addition is complete, react for 12-24 hours to obtain a reaction solution, and place the obtained reaction solution at 30-40° C. and vacuum dry for 8-10 hours to obtain a modified fluorosilicone resin; The obtained modified fluorosilicone resin is dissolved in a second organic solvent to prepare a modified fluorosilicone resin solution with a solid content of 30-60%; The fluorine-containing acrylic monomer is dodecafluoroheptyl methacrylate or / and perfluorobutyl ethyl methacrylate; The initiator is AIBN or BPO, the amount of the initiator is 0.1-2% of the monomer mass, and the mass ratio of the initiator to ethyl acetate in the initiator-ethyl acetate solution is 1:8-10; The mass ratio of the methacrylate acyloxypropyloxysilane, the ester-containing benzoxazine monomer and the fluorine-containing acrylate monomer is 8-15:5-12:18-25; The amount of solvent ethyl acetate used is 50-60% of the total mass of the monomers; The second organic solvent is ethyl acetate or dichloromethane; The modified nano-scale carbon-based material is obtained by modifying an oxidized nano-scale carbon-based material with silane; the carbon-based material is carbon black or carbon nanotubes.
2. A photothermal super-hydrophobic coating according to claim 1, characterized in that: The functional additives are two or three of a wetting and dispersing agent, a defoaming agent and a leveling agent.
3. A photothermal super-hydrophobic coating according to claim 1, characterized in that: The adhesion promoter is silane coupling agent Z-6121 or titanate coupling agent; the titanate coupling agent is triisostearyl isopropyl titanate or isopropyl tri(dioctyl pyrophosphate) titanate.
4. A photothermal super-hydrophobic coating according to claim 1, characterized in that: The filler is a mixture of two or more of heavy calcium, talcum powder, barium sulfate, sericite powder and carbon black.
5. A photothermal super-hydrophobic coating according to claim 1, characterized in that: The first organic solvent is one or more of butyl acetate, ethyl acetate or dichloromethane.
6. A photothermal super-hydrophobic coating according to claim 1, characterized in that: The wetting and dispersing agent is a nonionic wetting and dispersing agent or a fluorocarbon wetting agent; the defoaming agent is a mineral oil defoaming agent, an organosilicon defoaming agent or a polyether defoaming agent; and the leveling agent is an organosilicon oil leveling agent or a polyether leveling agent.
7. A photothermal super-hydrophobic coating according to claim 1, characterized in that: The specific preparation process of the modified nanoscale carbon-based material is as follows: The nano-scale carbon-based material is slowly added to the mixed strong acid in small amounts and multiple times, heated to 58-62°C under mechanical stirring, stirred for reaction for 12-24 hours, washed to neutrality, and dried to obtain the oxidized nano-scale carbon-based material; Ultrasonic dispersion of the obtained oxidized nano-scale carbon-based material in ethanol, adding a second silane coupling agent thereto under stirring, continuing stirring for 0.5 to 1 hour, filtering, washing with ethanol, and drying under vacuum to obtain a modified nano-scale carbon-based material; The mass ratio of the nano-scale carbon-based material, the mixed strong acid and the second silane coupling agent is 1:100~150:0.03~0.06; The mixed strong acid is obtained by mixing concentrated sulfuric acid and concentrated nitric acid in a mass ratio of 100:40-50.
8. A photothermal super-hydrophobic coating according to claim 7, characterized in that: The second silane coupling agent is one or more of silane coupling agents KH560, KH570 or KH550.
9. A method for preparing a photothermal super-hydrophobic coating according to claim 1, characterized in that: The following steps are involved: In parts by weight, 0.1-0.8 parts of an adhesion promoter, 15-25 parts of a filler and 25-35 parts of a first organic solvent are mixed, ground to less than 40 μm, filtered, and 30-40 parts of a modified fluorosilicone resin solution, 3-15 parts of a polypyrrole resin, 20-30 parts of a modified nanoscale carbon-based material, 0.05-0.1 parts of nano-silicon dioxide, and 3-5 parts of a functional additive are added thereto, stirred and dispersed evenly to obtain a light-heating super-hydrophobic coating.
Citation Information
Patent Citations
Benzoxazine resin-containing high temperature-resistant self-lubricating composite coating and preparation method thereof
CN103497671A
Benzoxazine modified organic silicon resin and preparation method and application thereof
CN111848959A
Low-surface-energy UV-LED curing environment-friendly coating glue and preparation method thereof
CN116004112A
Photo-thermal hydrophobic coating as well as preparation method and application thereof
CN117126599A
Cited By
Composite anti-icing coating with high hydrophobicity
CN120137473A